2010
DOI: 10.1007/s11270-010-0448-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Composition, Macronutrient Concentrations, and Carboxylating Enzymes in Relation to the Growth of Pinus halepensis Mill. When Subject to Ozone Stress

Abstract: We present here the effects of ambient ozone (O 3 )-induced decline in carbon availability, accelerated foliar senescence, and a decrease in aboveground biomass accumulation in the Aleppo pine (Pinus halepensis Mill.). Aleppo pine seedlings were continuously exposed in open-top chambers for 39 months to three different types of O 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The highest R 2 values were obtained with CO; however, there is no known direct effect of CO on plants, and therefore the causal mechanisms must involve another pollutant, most likely CO 2 or O 3 . Elevated atmospheric O 3 has been reported to affect plant δ 13 C by altering plant gas exchange and carbon isotope discrimination (Gessler et al 2009;Inclán et al 2011;Jäggi and Fuhrer 2007) directly through oxidant damage to guard cells and mesophyll membrane that decreases stomatal control (Torsethaugen et al 1999) or indirectly through changes in photosynthetic enzymes (such as Rubisco) and internal CO 2 concentrations (Ci) (Andersen 2003;Zheng et al 2002). Under elevated O 3 concentrations, plant δ 13 C may be enriched (Jäggi and Fuhrer 2007) or unchanged (Bassin et al 2009;Gessler et al 2009;Jäggi and Fuhrer 2007) depending on species and the complex effects of O 3 on gas exchange as well as local microclimate..…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest R 2 values were obtained with CO; however, there is no known direct effect of CO on plants, and therefore the causal mechanisms must involve another pollutant, most likely CO 2 or O 3 . Elevated atmospheric O 3 has been reported to affect plant δ 13 C by altering plant gas exchange and carbon isotope discrimination (Gessler et al 2009;Inclán et al 2011;Jäggi and Fuhrer 2007) directly through oxidant damage to guard cells and mesophyll membrane that decreases stomatal control (Torsethaugen et al 1999) or indirectly through changes in photosynthetic enzymes (such as Rubisco) and internal CO 2 concentrations (Ci) (Andersen 2003;Zheng et al 2002). Under elevated O 3 concentrations, plant δ 13 C may be enriched (Jäggi and Fuhrer 2007) or unchanged (Bassin et al 2009;Gessler et al 2009;Jäggi and Fuhrer 2007) depending on species and the complex effects of O 3 on gas exchange as well as local microclimate..…”
Section: Discussionmentioning
confidence: 99%
“…Wang and Pataki (2010) have reported correlation between plant δ 13 C and concentrations of CO 2 and other air pollutants like CO, O 3 , and NO 2 . Elevated atmospheric O 3 has been reported to affect plant δ 13 C by altering plant gas exchange and carbon isotope discrimination (Gessler et al 2009;Inclán et al 2011;Jäggi and Fuhrer 2007); however, no causal links have been found between plant δ 13 C and CO or NO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Inclán et al, 2011), Populus tremuloides (e.g. McGrath et al, 2010), hybrid poplar (Populus maximowizii  trichocarpa) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…6B), indicating that O 3 stress significantly inhibited photosynthesis and degraded photosynthetic pigments of A. ginnala . The inhibition of photosynthetic parameters might be associated with the fact that O 3 reduced the amount of carbon available for allocation by decreasing photosynthetic carbon assimilation (Inclán et al 2011), which partly explains the observed reduction in growth parameters (height, basal diameter and total biomass) of A. ginnala exposed to O 3 . Furthermore, the PCA showed that PC2 separated the effects of O 3 and C groups, mainly through growth and chlorophyll fluorescence parameters, such as basal diameter, RWC, F v / F m and Φ PSII (Fig.…”
Section: Discussionmentioning
confidence: 99%